Measuring timescales of magmatic evolution - Turner, Simon (2012)
Advances in analytical methods have provided new insights into the timescales of magmatic processes. Data on the abundances of U-series isotopes in bulk rocks and crystal separates indicate magma differentiation over thousands of years. Residence and differentiation times of silicic magmas based on single-crystal, in situ age data vary from 10,000 to 100,000 years, with abundant evidence for crystal recycling from previous intrusive episodes. Chemical zoning patterns in single crystals indicate that processes such as mixing and mingling of magmas and crustal assimilation may occur over much shorter timescales of months to decades. Quantifying the rates of magma generation, emplacement and differentiation constrains the processes involved and may contribute to the evaluation of volcanic hazards.